دور المقدرات الاستراتيجية في تعزيز استراتيجيات الانتاج الانظف دراسة تحليلية لاراء القادة الاداريين في عدد من المنظمات الصناعية في محافظة دهوك - سلطان, أ. د. حكمت رشيد; يوسف, أ. د. ميهفان شريف; محمد, أ. م. روش ابراهيم (Sulaimani Journal for Humanities, 2023)
Current research aims to recognize the reality of investigated industry organizations' possession of strategic capabilities and cleaner production technology in order to identify and support their strengths, In addition to identifying the role of strategic capacities available in promoting cleaner production strategies in investigated industry organizations.To answer the research questions raised in the research problem, the research adopted a hypothetical blueprint to measure the nature and impact of the relationship between each of its variables: independent (Strategic capacity) and dependent (cleaner production). The research community was represented by managerial and technical leaders in the research industry organizations, while a group of individuals working under several functional names, such as a general manager, a laboratory manager, a section manager, an engineer, a technical division manager and a production line officer, were selected to represent the research sample. A set of key hypotheses tested was formulated with the adoption of statistical software (SPSS V.26) for data obtained through the questionnaire form prepared for this purpose, and by answering the questions of respondents in the investigated industry organizations on the role of strategic capacities in promoting cleaner production strategies. A number of conclusions have been reached, the most important being: statistical analysis shows that there is a moral positive correlation and impact between strategic capabilities and cleaner production in the investigated industrial organizations. Therefore, whenever strategic capabilities and their dimensions are available in those organizations, this improves cleaner production strategies. One of the most important proposals presented by the research is the need for the investigated industry organizations to show continued interest in their strategic capacities, as they play a role in developing the Organization's ability to keep pace with the ongoing changes in its external environment and thus contribute to enhancing their adoption of appropriate cleaner production strategies.
Keywords: المقدرات الاستراتيجية ابعاد المقدرات الاستراتيجية الانتاج الانظف استراتيجيات الانتاج الانظف المنظمات الصناعية محافظة دهوك